Automated Lab attendance system (ALAS) by using students card - M Murugakandar, Raja Kumaran (2005)
Students Attendance system is important to the lecturers to assist them in reading students attendance in the class or lab. Other than that,it will help the lecturers to know the percentages of attendance of the entire student.The main purpose of this system is to help the lecturers to take the students attendance systematically instead of using manual system.The Automated Lab Attendance System (ALAS) is developed based on KUKTEM environment.This system will not only will help the lecturer to take attendance of students but also help the Lab Administrator to control the usage of the lab.This system is developed using Microsoft Visual Basic.NET and Microsoft SQL Server 2000.Generally,this system is expected to be one of the systems that help the Lab Administrator to manage the time of lab usage and systematic computerized attendance system.